The international integration of money markets in the central and east European accession countries: deviations from covered interest parity, capital controls and inefficiencies in the financial sector - Axel Jochem; Sabine Herrmann (Deutsche Bundesbank, 2003)
Based on the concept of covered interest parity it is shown that the money markets in Poland, the Czech Republic, Hungary, and the Slovak Republic meanwhile display a high degree of international integration with the euro area. Integration has strengthened continuously in the review period of 1999 to mid 2002. The segmentation that could still be observed stems from both restrictions on the short-term movement of capital and the limited development of the financial sectors in the four accession countries. While almost all capital controls have since been removed and will no longer play a role after accession to the EU, the implementation and transmission of the single monetary policy within the Eurosystem will possibly be impeded, if the financial sectors in CEE are then still underdeveloped. – – Basierend auf dem Konzept der gedeckten Zinsparität wird gezeigt, dass die Geldmärkte in Polen, der Tschechischen Republik, Ungarn und der Slowakei inzwischen einen hohen Grad an internationaler Integration mit dem Euro-Raum aufweisen. Die Integration hat sich im Untersuchungszeitraum von 1999 bis Mitte 2002 kontinuierlich verstärkt. Für die noch zu beobachtende Segmentierung sind sowohl Beschränkungen des kurzfristigen Kapitalverkehrs als auch die geringe Entwicklung der Finanzsektoren in den Beitrittsländern verantwortlich. Während Kapitalverkehrskontrollen inzwischen fast vollständig abgebaut sind und nach einem EU-Beitritt keine Rolle mehr spielen werden, könnte innerhalb des Eurosystems die Implementierung und Transmission der gemeinsamen Geldpolitik beeinträchtigt werden, wenn die Finanzsektoren in Mittel- und Osteuropa noch unterentwickelt sind.
Keywords: 330; Geldmarkt; Internationaler Finanzmarkt; Marktintegration; Zinsparität; Schätzung; Osteuropa; Polen; Tschechische Republik; Ungarn; Slowakei; EU-Staaten